Injury risks associated with tackling in rugby union. Issue 3 (22nd August 2008) - Fuller, Colin W; Ashton, Tony; Brooks, John H M; Cancea, Rebecca J; Hall, John; Kemp, Simon P T
Abstract : Objective: To examine factors associated with tackles in rugby union and to assess their impact on the risk of injury. Design: Two-season (2003/2004 and 2005/2006) prospective cohort design with video analysis. Setting: 13 English Premiership clubs. Participants: 645 players. Main outcome measure: RR (95% CI) calculated by comparing the frequency of occurrence of risk factors in a cohort of players injured during tackles with their frequency of occurrence in tackles in general play. Risk factors: Playing position; player's speed, impact force, head position, head/neck flexion and body region struck in the tackle; sequence, direction and type of tackle; and location and type of injury. Results: High-speed going into the tackle, high impact force, collisions and contact with a player's head/neck were identified as significant (p<0.01) risk factors for ball carriers (BCs) and tacklers. Midfield backs were significantly (p<0.01) more prone to injury when tackling than other players. Relatively few tacklers were penalised by referees for collision tackles (general play: 2.0%; injured players: 3.3%) and tackles above the line of the shoulder (general play: 5.9%; injured players: 16.7%). Conclusions: Advice in national and international injury prevention programmes for reducing the risk of injury in tackles is strongly supported by the results obtained from this study. These programmes should be reviewed, however, to provide specific advice for each type of tackle. Stricter implementation of the Laws of Rugby relating to collisions and tackles above the line of the shoulder may reduce the number of head/neck injuries sustained by BCs.